2012
DOI: 10.17660/actahortic.2012.962.85
|View full text |Cite
|
Sign up to set email alerts
|

Response of Low and Medium Vigour Rootstocks for Peach to Biotic and Abiotic Stresses

Abstract: New low and medium vigour Prunus rootstocks compatible with peach cultivars were evaluated under controlled and in field conditions against biotic and abiotic stress factors. Most rootstocks exhibited different levels of resistance to the root-knot nematode Meloidogyne javanica. The plum hybrids ʻPAC 9801-02ʼ and ʻKrymsk 86ʼ ® were the only rootstocks that exhibited a moderate resistance to the lesion nematode. All rootstocks showed a high sensitivity to crown gall. The low vigour plums ʻEvricaʼ and ʻKrymsk 1ʼ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Different studies have reported that the highest fruit weight was induced by the most invigorating rootstocks (Albás et al, 2004;Legua et al, 2011;Font i Forcada et al, 2012), although Pinochet et al (2012) showed that the less vigorous rootstock Krymsk® 1could induce bigger fruit size. However, growing conditions and cultural practices could account for these differences.…”
Section: Discussionmentioning
confidence: 96%
“…Different studies have reported that the highest fruit weight was induced by the most invigorating rootstocks (Albás et al, 2004;Legua et al, 2011;Font i Forcada et al, 2012), although Pinochet et al (2012) showed that the less vigorous rootstock Krymsk® 1could induce bigger fruit size. However, growing conditions and cultural practices could account for these differences.…”
Section: Discussionmentioning
confidence: 96%
“…'Rootpac-40' and 'Rootpac-20' are considered to be less vigorous than 'Garnem', which opens the possibility to establish more efficient production systems in high-density orchards [11]. However, their adaptability to warm Mediterranean environments with the presence of soil borne pathogens and unfavorable soil conditions may limit their use [12]. Significant effects of insufficient chilling accumulation on peach cultivars were somewhat attenuated by rootstock type [13].…”
Section: Introductionmentioning
confidence: 99%
“…A Prunus rootstock breeding program for adaptation to Mediterranean growing conditions is being carried out at the Experimental Station of Aula Dei (CSIC), (Moreno, 2004). Selected rootstocks with good agronomic performance and tolerance to abiotic and biotic stresses have been made available (Pinochet et al, 2012;Mestre et al, 2015Mestre et al, , 2017. The present work aimed to evaluate the effect of different rootstocks budded with 'Big Top' nectarine on agronomical features (TCSA, yield, cumulative yield, and yield efficiency) and fruit quality traits in a heavy, calcareous soil when grown under root asphyxia conditions.…”
mentioning
confidence: 99%